2020
DOI: 10.1016/j.jcat.2020.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of hierarchical pores with strong Brønsted acid sites on SAPO-34 catalysts for the glycerol dehydration to acrolein

Abstract: The hierarchical SAPO-34 zeolites have been prepared with the simultaneous generation of strong Brønsted acid sites (BASs) via a post-synthetic method, which allows the cooperation of the positive effects of both porous structure and acidity in the dehydration of glycerol to acrolein. The cooperation of strong BASs only in enhancing the acrolein selectivity and the hierarchical pores in improving the glycerol conversion has significantly increased the overall acrolein yield to 89.8% on the hierarchical SAPO-34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…The identified peak is a typical peak for Al IV species (bridging Si−OH−Al groups) in zeolites. 20,29,35,39 Contributing from the humidity penetration during the MAS measurement, the line broadening is less severe (from 30 to 65 ppm) compared to the previously reported research. 32 After the rehydration process (Figure 2b), no observable change can be identified in the 27 Al NMR spectrum except the line narrowing of the Al IV peak, indicating no extraframework Al species existing on zeolites.…”
Section: Resultsmentioning
confidence: 51%
See 2 more Smart Citations
“…The identified peak is a typical peak for Al IV species (bridging Si−OH−Al groups) in zeolites. 20,29,35,39 Contributing from the humidity penetration during the MAS measurement, the line broadening is less severe (from 30 to 65 ppm) compared to the previously reported research. 32 After the rehydration process (Figure 2b), no observable change can be identified in the 27 Al NMR spectrum except the line narrowing of the Al IV peak, indicating no extraframework Al species existing on zeolites.…”
Section: Resultsmentioning
confidence: 51%
“…The h-ZSM-5 (50) and Al/h-ZSM-5 (50) zeolites have a hysteresis loop that can provide evidence for additional mesoporous structure. 20,35,36 The pore size distributions of h-ZSM-5 (50) and Al/h-ZSM-5 (50) zeolites have been further analyzed by using BJH methods. As presented in Figure S2b, both the h-ZSM-5 (50) and Al/h-ZSM-5 (50) zeolites have an average mesopore size of around 4−6 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The special chemical structure of zeolite forms many holes and channels, which makes it to have a larger specific surface area and more adsorption sites. Therefore, zeolite has a strong adsorption property 15 . The isothermal characteristics of zeolite adsorption, 16,17 adsorption kinetics, 18 and adsorption thermodynamics were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, zeolite has a strong adsorption property. 15 The isothermal characteristics of zeolite adsorption, 16,17 adsorption kinetics, 18 and adsorption thermodynamics were analyzed. It can be found that zeolite can be considered for the adsorption of radioactive wastes due to the good adsorption property of zeolite.…”
Section: Introductionmentioning
confidence: 99%